Hatching and mortality of meloidogyne enterolobii under the interference of entomopathogenic nematodes in vitro - Damascena, Alixelhe Pacheco [UNESP]; Ferreira, Júlio César Antunes [UNESP]; Costa, Marylia Gabriella Silva [UNESP]; de Araujo Junior, Luis Moreira; Wilcken, Silvia Renata Siciliano [UNESP] (De Gruyter, 2019)
Plant parasitic nematodes have become one of the main problems in the tomato cultivation. Among these, Meloidogyne enterolobii presents great challenges to the farmer, since it is a polyphagous species and difficult to control. The entomopathogenic nematodes (EPNs) present as potential for biological control of this pathogen. The objective of the study was to evaluate the interference of EPNs S. brazilense, S. feltiae, S. rarum, H. amazonensis and H. bacteriophora on hatching and mortality of M. enterolobii. 500 eggs of this nematode and 1.000 infective juveniles of each EPN species were placed in a plastic pot totaling 25 mL of suspension and kept in an incubator at 25°C. The number of juveniles hatched in the suspension was counted every 2 days, until 10 days. After 10 days of evaluations, the remaining suspension (15 mL) containing M. enterolobii and EPNs was inoculated into Rutgers tomato seedlings. The suspension contained approximately in 300 eggs of M. enterolobii occasional juveniles and 600 IJ of each nematode species. Sixty days after inoculation were evaluated gall indexes, egg mass indexes, total number of eggs and juveniles of M. enterolobii and reproductive factor was calculated. In the mortality experiment, 500 infective juveniles of M. enterolobii and 1.000 juveniles of each EPN species were placed in a plastic pot totaling 25 mL of suspension. The evaluation of juvenile mortality was performed by counting of the mobile and immotile nematodes, by adding two drops of NaOH to the nematode suspension. It was verified that on the 10th day all ENPs provided reduction in the hatching of M. enterolobii. In the pot experiment it was found thato gall index, egg mass indexm, nematodes total number and reproduction factor were significantly reduced in treatments with all species of EPNs tested. However, in the mortality test, only EPNs S. brazilense and S. rarum provided mortality on the second day and H. bacteriophora affected mortality on the 4th day. In the other evaluations, there was no statistical difference. The results highlight the potential of the use of EPNs in programs of integrated management of M. enterolobii in tomato.
Keywords: Biological control; Entomopathogens; Management; Phytopathogenic nematodes